Influences of channel bed morphology on flow structures in continuous curved channels - Liu, Yujiao; Chai, Yuanfang; Yu, Minghui; Zhou, Yinjun (Frontiers in Environmental Science, 2024)
The formation of bars and pools, characterized by concave and convex bed morphology, is a typical feature of curved rivers. The channel bed morphology has a significant influence on the flow structures in curved channels. Based on data from physical model experiments, this study employs the RNG k-ε model and the VOF (Volume of Fluid) method to perform three-dimensional numerical simulations of flow in continuous curved channels. By comparing the variations in flow structures between channels with a flat bed and channels with bars and pools, the results show that the presence of bars and pools leads to an increase in longitudinal flow velocity on the convex bank side near the entrance of the upstream bend, while in the downstream bend it is opposite. The high-velocity region shifts slower towards the concave bank along the bend. The presence of point bars weakens the circulation near the convex bank in the upstream bend, resulting in a smaller circulation intensity. The decrease in circulation intensity is the largest (-23.91%) at the apex of the bend. In the downstream bend, the remaining circulation from the upstream bend attenuates slower in the pool and has a greater impact distance, increasing the circulation intensity in the downstream bend. The section near the bend entrance shows the largest increase in circulation intensity, with a rate of 128.18%. The unevenness of the bed topography increases the unevenness of the bed shear stress in the downstream bend. The findings of this study contribute to a deeper understanding of the complex flow structures and evolution trends in natural curved rivers, providing scientific basis for the management of curved river channels.